Analysis of the Crime of Human Trafficking in Indonesia (Case Study: Human Trafficking with Marriage Mode in West Kalimantan) - Syifa Amalia; Robby Syahputra; Alfatih Jagad (Faculty of Law, University of Mataram, 2021)
The condition of globalization has both positive and negative impacts on people in Indonesia. Many new things were done to gain an advantage for a certain party. One of them is the emergence of cases of human trafficking with various modes. These people trade often look for weak targets to target—likely women and children. Trafficking in persons is now categorized as a severe crime. So, the need for strict law enforcement for this crime is expected to be eradicated, either reduced or even eliminated. This research aims to analyse the factors causing women and children as the main target of human trafficking, the law enforcement and preventive measures of human trafficking in Indonesia. The research method uses a descriptive qualitative approach and is supported by secondary data based on available literature to explore case studies of human trafficking. How to solve problems, protect and enforce the law in the international sphere and Indonesia. The main factors that encourage human trafficking are economic factors or poverty, law enforcement factors. Women and children are the main target of this crime because they are considered weak and belong to a vulnerable group. The Law enforcement and preventive measure of human trafficking in Indonesia conducted under Human Trafficking Act and Immigration Act.